Shifts in connectivity during procedural learning after motor cortex stimulation: A combined transcranial magnetic stimulation/functional magnetic resonance imaging study. (January 2016) - Steel, Adam; Song, Sunbin; Bageac, Devin; Knutson, Kristine M.; Keisler, Aysha; Saad, Ziad S.; Gotts, Stephen J.; Wassermann, Eric M.; Wilkinson, Leonora
Abstract: Inhibitory transcranial magnetic stimulation (TMS), of which continuous theta burst stimulation (cTBS) is a common form, has been used to inhibit cortical areas during investigations of their function. cTBS applied to the primary motor area (M1) depresses motor output excitability via a local effect and impairs procedural motor learning. This could be due to an effect on M1 itself and/or to changes in its connectivity with other nodes in the learning network. To investigate this issue, we used functional magnetic resonance imaging to measure changes in brain activation and connectivity during implicit procedural learning after real and sham cTBS of M1. Compared to sham, real cTBS impaired motor sequence learning, but caused no local or distant changes in brain activation. Rather, it reduced functional connectivity between motor (M1, dorsal premotor & supplementary motor areas) and visual (superior & inferior occipital gyri) areas. It also increased connectivity between frontal associative (superior & inferior frontal gyri), cingulate (dorsal & middle cingulate), and temporal areas. This potentially compensatory shift in coupling, from a motor-based learning network to an associative learning network accounts for the behavioral effects of cTBS of M1. The findings suggest that the inhibitory TMS affects behavior via relatively subtle and distributed effects on connectivity within networks, rather than by taking the stimulated area "offline".